A process for academic societies to develop scientific statements and white papers: experience of the Pediatric Cardiac Intensive Care Society. (4th December 2018) - Reddy, Sushma; Polito, Angelo; Staveski, Sandra; Dalton, Heidi
Abstract: There are substantial knowledge gaps, practice variation, and paucity of controlled trials owing to the relatively small number of patients with critical heart disease. The Pediatric Cardiac Intensive Care Society has recognised this knowledge gap as an area needing a more comprehensive and evidence-based approach to the management of the critically ill child with heart disease. To address this, the Pediatric Cardiac Intensive Care Society created a scientific statements and white papers committee. Scientific statements and white papers will present the current state-of-the-art in areas where controversy exists, providing clinicians with guidance in diagnostic and therapeutic strategies, particularly where evidence-based data are lacking. This paper provides a template for other societies and organisations faced with the task of developing scientific statements and white papers. We describe the methods used to perform a systematic literature search and evidence rating that will be used by all scientific statements and white papers emerging from the Pediatric Cardiac Intensive Care Society. The Pediatric Cardiac Intensive Care Society aims to revolutionise the care of children with heart disease by shifting our efforts from individual institution-based practices to national standardised protocols and to lay the ground work for multicentre high-impact research directions.